Sexual Behaviour and Reproductive Health of Women in North Sulawesi Province: A Secondary Data Analysis - Indriani Yauri; Brigitte Inez Maitimo; Vervando J. Sumilat; Junita J J. Koilam (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: Although health promotion strategies have been made to promote reproductive health, women’s reproductive health problems have not dropped significantly. This study aimed to examine the relationship between early sexual behavior and reproductive health of women of reproductive-aged 15-49 years old for North Sulawesi Province, Indonesia. Methods: Descriptive correlational design was used to examine the relationship between the age of first sexual intercourse and pregnancy complications, decision making about the use of birth control, and knowledge about HIV-AIDS. Data were obtained from 585 women aged 15-49-year-old selected from the 2017 Indonesia Demographic and Health Survey (SDKI 2017). Results: Cramer’s V correlation coefficient showed a strong correlation between age at first sexual intercourse and pregnancy complications and moderate correlation between decision making about the use of birth control, and knowledge about HIV-AIDS. Forty percent of sexually active women were 10-19 years old. In addition, decisions about the use of contraceptive strategies among those ages have the potential to be not users in accordance with rational contraception use because they might not seek health workers’ advice. This study also found a low proportion of women understood HIV transmission. Conclusions: Findings from this study affirm the hypothesis that women’s sexual behavior correlates with their reproductive health. Therefore, improving sexual behavior may improve reproductive health. These findings also may be used to inform the effectiveness of the implemented reproductive health programs in North Sulawesi Province. Several culturally sensitive strategies are recommended to overcome problems and improve reproductive health.